Study on the Influencing Factors of Knowledge, Attitudes and Practice About Tuberculosis Among Freshmen in Jiangsu, China: A Cross-Sectional Study - Du G; Li C; Liu Y; Tu F; Yang R; Li R; Shen H; Li W (Infection and Drug Resistance, 2022)
Guoping Du,1,* Chao Li,2,* Yangyang Liu,3,* Fulai Tu,3 Ruizhe Yang,4 Rui Li,3 Hongbing Shen,2 Wei Li5 1Department of General Practice, Southeast University Hospital, Nanjing, Jiangsu, People’s Republic of China; 2Department of Epidemiology, Center for Global Health, School of Public Health, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 3Key Laboratory of Environmental Medicine Engineering, Department of Epidemiology and Health Statistics, School of Public Health, Southeast University, Nanjing, Jiangsu, People’s Republic of China; 4Department of Prevention and Health Care, Children’s Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 5Department of Quality Management, Children’s Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Li, Department of Quality Management, Children’s Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China, Tel/Fax +86 025 52862911, Email weili126@126.com Hongbing Shen, Department of Epidemiology, Center for Global Health, School of Public Health, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China, Tel/Fax +86 025 86868409, Email hbshen@njmu.edu.cnBackground: Adolescents aged from 19 to 22 are the main high-risk population of pulmonary tuberculosis (PTB). This study aimed to understand the current status of knowledge, attitudes and practices (KAP) about TB among freshmen from Jiangsu colleges and universities. Analyze its influencing factors and explore the interrelationships of KAP. This provides a basis for building a reversing mechanism for health education on tuberculosis prevention and treatment in middle and high schools.Methods: A multistage randomly was used to select freshmen to conduct this online survey. The χ2 test was used to compare the rates. Construct linear regression model, logistic regression model, decision tree model and random forest model, use grid search to adjust the parameters of the model, and use multiple models to explore the influencing factors of the overall awareness rate of students’ core knowledge of tuberculosis.Results: A total of 6980 freshmen in colleges and universities were investigated. The total awareness rate was 89.02%, and the awareness rate of all core knowledge about TB was 58.94%. It is characterized by general demographic data, and all core knowledge is known as a label to establish a model, based on the f1- of the four models The score believes that the random forest model has the best fitting effect, and the ranking of the influencing factors included in the model is school type (0.72) >father’s education (0.15) >family monthly income (0.03) >mother’s education, gender, region (0.02); a structural equation model is established, and the modified knowledge and attitude path coefficient is 0.29 (P< 0.05); the attitude and behavior path coefficient is 0.64 (P< 0.05).Conclusion: The total awareness rate of core knowledge of Jiangsu college freshmen reaches the national requirements, but the overall awareness rate is low. It is necessary to strengthen the health education of tuberculosis for those with identified risk factors.Keywords: knowledge, attitudes and practices, tuberculosis, freshmen